Network reconfiguration for loss minimization in power distribution system using sensitivity analysis: article / Muhammad Hanis Hilmi Johari - Johari, Muhammad Hanis Hilmi (2013)
This paper present the two stage method for reduce the power loss in power distribution system. The study involved the implementation of sensitivity analysis in order to minimum loss due to distribution system configuration. This method uses the loss sensitivity of transfer line with respect to the impedance of candidate branches in the stage I and branch exchange method in the stage II. In the stage I, the reconfiguration of power distribution system start with all candidate switches to be closed forming a meshed system, then the switches will be opened based on loss sensitivity analysis until the power distribution system forming a radial network structure and all load condition must have connectivity. In the stage II, implementation of branch exchange method is used to improve the solution found by the first stage. This method was implemented on 16-bus system and 33-bus system for demonstrating the effectiveness of proposed method.